Geographic variation in germination of the Enterolobium cyclocarpum of the coast of Oaxaca, Mexico - Viveros-Viveros, Héctor; Quino-Pascual, Karen; Velasco-García, Mario Valerio; Sánchez-Viveros, Gabriela; Velasco Bautista, Efraín (BOSQUE, 2017)
Enterolobium cyclocarpum is recommended in reforestation and ecological restoration programs. However, before starting large-scale plantations some germination parameter form different seed sources should be identified, which can be used for plant production in each location or use elsewhere. In this paper, the variation of some germination parameters from ten provenances of E. cyclocarpum from the Coast of Oaxaca, Mexico was explored. Four germination parameters: germination capacity, mean daily germination, peak value and germination value were assessed in the laboratory. From information about geographical location and altitude above sea level of each provenance, climatic variables were obtained and afterward correlated with the germination parameters. Significant differences among provenances were detected for all of the germination parameters. There was not significant relationship among germination parameters and geographic variables, but there was a positive relationship between germination capacity and the proportion of precipitation falling during summer; and between mean daily germination and the total precipitation that falls during the growing season. The germinative capacity varied from 28.2 to 90 %; it depended on provenance. The low germination of some provenances can cause problems in their permanence and conservation.